(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The performance and reliability of two-stage combination electric motors largely depend on the quality and behavior of their magnetic components. In this study, we investigate the inspection methods and operational implications of magnetic materials and assemblies within a two-stage electric motor system. Emphasis is placed on the analysis of core losses, magnetic flux distribution, and material integrity under dynamic operating conditions. Advanced non-destructive testing techniques such as magnetic flux leakage (MFL), eddy current testing, and thermographic analysis are evaluated for their effectiveness in detecting defects, misalignments, and degradation in laminated cores and permanent magnets. The study also explores the influence of magnetic component quality on efficiency, torque production, and thermal stability during staged transitions in the motor’s operation. Results indicate that rigorous magnetic inspection, integrated into the design and maintenance process, significantly enhances system performance and prolongs motor lifespan. These findings provide a critical foundation for optimizing inspection protocols in high-performance electric motor applications.